Transformasi Teknologi Inovatif Produksi Biochar Berbasis Biomassa untuk Pemberdayaan Santri dan Petani dalam Mewujudkan Ekonomi Hijau di Samarinda - Ida Rosanti; Purbawati Purbawati; Sri Endayani; Mad Yusup; Hadi Safwan; Moh Amirrudin; Wita Vadillah (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service initiative aimed to empower Islamic boarding school students and local farmers in Lempake, Samarinda, through the transfer of innovative biochar production technology utilizing biomass waste. The target community faces significant challenges, including poor soil fertility, land degradation from post-mining activities, and underutilization of abundant organic waste. The introduced biochar technology employs a simple pyrolysis process using Kon-Tiki Kilns to convert agricultural residues into porous, carbon-rich material, enhancing soil structure, nutrient retention, and water-holding capacity while reducing reliance on chemical fertilizers. The Program activities included field observations, awareness campaigns, hands-on training, technology demonstrations, mentoring, and evaluation, with Pesantren Rahmatullah serving as a strategic hub for education and local innovation. The results showed significant improvements in participants' knowledge and skills in producing and applying biochar, stimulating community-based business opportunities, enhancing soil.